Interaction of rhodium(III) chloride complexes with formaldehyde into the sulphate and chloric solutions. - T. M. Buslaeva; G. M. Voldman; D. A. Lapshin; N. M. Bondar (Тонкие химические технологии)
Interaction of Rhodium(III) Chloride complexes with Formaldehyde into the sulphate and chloric solutions has been studied. Probably stages of reducing process that proceeds with metal Rhodium formation has been suggested. Influence of initial Rhodium, Formaldehyde and Hydrochloric acid concentration on the rate of each stage and on the extraction extent of valuable metal into a solid phase has been observed.